Реалізація можливостей ефективнішого використання кристалічних матеріалів на основі нетривіальної кутової геометрії екстремумів п’єзооптичного ефекту - Дем’янишин, Н. М.; Андрущак, А. С.; Бурий, О. А.; Мицик, Б. Г.; Demyanyshyn, N.; Andrushchak, A.; Buryy, O.; Mytsyk, B. (Видавництво Львівської політехніки, 2018)
Виявлено можливості ефективнішого практичного використання кристалічних матеріалів різних класів симетрії за рахунок аналізу просторової анізотропії та побудови вказівних чи екстремальних поверхонь п’єзооптичного ефекту для цих кристалів. На прикладі кристалів ніобату літію (клас симетрії 3m), вольфрамату кальцію (4/m) і тригліцинсульфату (2/m) показано, що п’єзооптичний ефект у цих кристалах істотно анізотропний як за знаком, так і за абсолютною величиною. Напрямки екстремумів п’єзооптичного ефекту не збігаються з кристалофізичними осями та визначаються нетривіальними кутами, які зумовлені класом симетрії досліджуваного матеріалу та можуть бути розраховані за значеннями їхніх п’єзооптичних коефіцієнтів.

The opportunities of the most efficient practical application of crystalline materials of different symmetry are found by the analysis of the spatial anisotropy and the construction of the indicative or extreme surfaces of piezo-optic effect in these crystals. The examples of lithium niobate (symmetry class 3m), calcium tungstate (4/m) and triglycine sulfate (2/m) show that the piezo-optic effect in these crystals is essentially anisotropic both on the sign and the absolute value. The directions of the piezo-optic effect extremes do not coincide with the crystal-physics axis and are determined by non-trivial angles which, in turn, are defined by symmetry class of the investigated material and can be calculated from the values of the piezooptic coefficients. The main principles of construction of 3D surfaces describing the optical effects induced by mechanical stress are shown in this paper for the cases of uniaxial and biaxial crystals. The examples of main relationships which are used for the construction and the analysis of such surfaces are given. The geometrical conditions of piezo-optic interaction with the maximal achievable value of the effect are determined for the specific crystalline materials. As it is proven, the full analysis of the anisotropy of the induced effects in crystals requires the construction of both the indicative and extreme surfaces as well as using of the analytical and numerical methods of determination of the maximal manifestation of piezooptic effect for the optimal choice and using of such functional materials in sensing elements of piezo-optic and acousto-optic devices. It is emphasized, that the construction and the analysis of these surfaces require the experimental determination of all non-zero components of the elasto-optic matrices for the investigated crystals; for this matter the wide list of publications dedicated to the methods of the investigation of piezo-optic effect in crystals with different symmetry is given.
Realization of more efficient application opportinities for crystalline materials based on the non-trivial angular geometry of the piezo-optic effect extremes
Keywords: п’єзооптичний ефект; просторова анізотропія; вказівні та екстремальні поверхні; piezo-optic effect; spatial anisotropy; indicative and extreme surfaces; 535.551; 548.0